Composite Growth Factor Supplementation Strategies to Enhance Tenocyte Bioactivity in Aligned Collagen-GAG Scaffolds - Caliari, Steven R. (Mary Ann Liebert, Inc., 2013)
Biomolecular environments encountered in vivo are complex and dynamic, with combinations of biomolecules presented in both freely diffusible (liquid-phase) and sequestered (bound to the extracellular matrix) states. Strategies for integrating multiple biomolecular signals into a biomimetic scaffold provide a platform to simultaneously control multiple cell activities, such as motility, proliferation, phenotype, and regenerative potential. Here we describe an investigation elucidating the influence of the dose and mode of presentation (soluble, sequestered) of five biomolecules (stromal cell-derived factor 1α [SDF-1α], platelet-derived growth factor BB [PDGF-BB], insulin-like growth factor 1 [IGF-1], basic fibroblast growth factor [bFGF], and growth/differentiation factor 5 [GDF-5]) on the recruitment, proliferation, collagen synthesis, and genomic stability of equine tenocytes within an anisotropic collagen-GAG scaffold for tendon regeneration applications. Critically, we found that single factors led to a dose-dependent trade-off between driving tenocyte proliferation (PDGF-BB, IGF-1) versus maintenance of a tenocyte phenotype (GDF-5, bFGF). We identified supplementation schemes using factor pairs (IGF-1, GDF-5) to rescue the tenocyte phenotype and gene expression profiles while simultaneously driving proliferation. These results suggest coincident application of multi-biomolecule cocktails has a significant value in regenerative medicine applications where control of cell proliferation and phenotype are required. Finally, we demonstrated an immobilization strategy that allows efficient sequestration of bioactive levels of these factors within the scaffold network. We showed sequestration can lead to a greater sustained bioactivity than soluble supplementation, making this approach particularly amenable to in vivo translation where diffusive loss is a concern and continuous biomolecule supplementation is not feasible.